Global climate change and cities: the insertion of the problem into local public policies - Orsi, Rafael Alves [UNESP] (Univ Federal Espirito Santo, 2023)
Among the various environmental problems that the contemporary world faces, the global climate changes has been widely debated and it presents itself like center of political tensions at different scales, which result in slow progress towards their equation. It is clear that the magnitude of the problem requires articulated actions among different actors and at several scales. From these concerns, this paper focused in the local scale, overall the medium cities. It aims analyze the insertion of the environmental questions, especially the climate changes, in the municipal director plans in Araraquara/SP and Sao Carlos/SP cities. By the content analyze of municipal laws, which institutes the director plans, and using the key words, it is possible verify that despite the environmental concerns in the plans, the climate changes appears like secondary issue. This fact towards needs to more attention with this question in the local scale.
Keywords: climate changes; director plan; medium cities; public policies